Hakikat Manusia dalam Ilmu Pendidikan Islam dan Relevansinya dengan Sistem Pendidikan di Indonesia - Yulinda Sari; Siti Roudhotul Jannah; Shinta Dewi Masitoh; Fitri Istiqomah (Bulletin of Indonesian Islamic Studies, 2023)
This paper analyzes the nature of humans in educational science and examines the relevance of human nature within the context of educational subjects in Indonesia. The study utilizes a qualitative library research approach, and data collection is conducted through documentation techniques. The researchers gather data from relevant books and journal articles, focusing on information that aligns with the theme and objectives of the study. Validation of the data is carried out using triangulation techniques. The findings indicate that understanding human nature forms the foundational basis for the development of Islamic educational science. Humans are not just biological or social beings; they are also spiritual and morally responsible. The goal of education in Islam is to refine human nature, develop reasoning, and shape character, enabling individuals to fulfill their roles as servants of Allah and as caliphs on earth. In the context of Indonesia, this understanding can align with the values of Pancasila, the 1945 Constitution, and local culture. An education system oriented towards the development of well-rounded individuals will effectively address contemporary challenges while preserving the nation's identity.